Conversion of percutaneous transhepatic biliary drainage to endoscopic ultrasound‐guided biliary drainage - Shinichi Morita (Wiley, 2021)
Abstract Introduction Percutaneous transhepatic biliary drainage (PTBD) is a useful alternative treatment for malignant biliary obstruction (MBO) when patients have difficulty with endoscopic transpapillary drainage. We examined the feasibility of conversion of PTBD to endoscopic ultrasound‐guided biliary drainage (EUS‐BD) in patients with MBO unsuited for endoscopic transpapillary biliary drainage. Methods This retrospective study included patients who underwent conversion of PTBD to EUS‐BD between March 2017 and December 2019. Eligible patients had unresectable MBO, required palliative biliary drainage, and were not suited for endoscopic transpapillary drainage. Initial PTBD had been performed for acute cholangitis or obstructive jaundice in all patients. EUS‐BD was performed following improvements in cholangitis. Sixteen patients underwent conversion of PTBD to EUS‐BD. We evaluated technical success, procedure time, clinical success (defined as subsequent external catheter removal), adverse events (AEs), time to recurrent biliary obstruction (TRBO), and re‐intervention rates. Results Technical success was achieved in all patients (100%). The median procedure time was 45.0 minutes (interquartile range [IQR] 30.0–50.0 minutes). Clinical success was achieved in all patients (100%). There were mild early AEs in two patients (12.5%) (acute cholangitis: 1, bile peritonitis: 1), which improved with antibiotic administration alone. Recurrent biliary obstruction (RBO) occurred in six patients (37.5%). Kaplan‐Meier analysis revealed a 50% TRBO of 95 days (IQR 41–246 days). Endoscopic treatment was possible in all RBO cases, and repeat PTBD was not required. Conclusions Conversion of PTBD to EUS‐BD for the management of MBO is both feasible and safe. This approach is expected to be widely practiced at centers with little experience in EUS‐BD.